Epiophlebia laidlawi daliensis, a new subspecies from Hengduan Mountains in Yunnan (Insecta, Odonata, Epiophlebiidae) - Yang, Guo-Hui; Wei, Yun-Yang; Li, Zi-Feng; Song, Rui-Bin; Wen, Yu-Chuan; Li, Xiao-Long; Zi, Dong-Dong; Lyu, Xue-Mei; Zhang, Hao-Miao (Zootaxa, 2025)
A new subspecies Epiophlebia laidlawi daliensis Zhang, Yang, Wei & Lyu, subsp. nov. is described from adult and larval specimens collected at Mt Cangshan in the Hengduan Mountains, Dali Bai Autonomous Prefecture, Yunnan, China. The holotype male was collected by Hao-miao Zhang and Rui-bin Song on 22 May 2022. Both sexes and larva of the new subspecies are compared with those of Epiophlebia l. laidlawi Tillyard, 1921 and E. superstes (Selys, 1889). A total of 15 sequences of ITS1 and 17 sequences of ITS2 were analysed and used for the phylogenetic comparisons. According to this analysis, E. l. daliensis subsp. nov. and E. l. laidlawi share a very close phylogenetic relationship, while E. l. daliensis, subsp. nov. and E. superstes are genetically more distant from one another than are E. l. laidlawi and E. superstes. Both neighbor-joining (NJ) and maximum likelihood (ML) methods produced consistent phylogenetic trees, with all E. l. daliensis specimens clustering with E. l. laidlawi. The existence of the named ‘species’ E. sinensis Li & Nel, 2012 (which in molecular analyses is retrieved within E. superstes) is considered doubtful, hence it is not considered here. Its status will be evaluated in another publication.